Evaluation of Fresh Graduate Recruitment Using the CIPP Model at PT Prima Sarana Gemilang - Mohammad Burhannudin (CV Edujavare Publishing, 2026)
This study aims to evaluate the recruitment strategy of the Prima Management Development Program at PT Prima Sarana Gemilang using the Context, Input, Process, Product evaluation model. The program was developed as a company strategy to recruit and prepare potential employees, especially fresh graduates, to support operational needs in the mining industry. This study employed a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. Research informants consisted of the Human Resources General Manager, Talent Acquisition Supervisor, and participants of the Prima Management Development Program selected using purposive sampling techniques. The results showed that the program was aligned with the company’s needs in building a talent pipeline and supporting workforce regeneration. The company has also implemented a relatively structured recruitment system through standard operating procedures, digital recruitment media, and competency-based selection stages. However, several obstacles were still identified, including limited recruiters, inconsistent candidate assessment standards, changes in selection schedules, and insufficient communication with candidates during the recruitment process. In addition, several fresh graduate participants still required strengthening of technical competencies and adaptation to the mining industry work culture. Overall, the recruitment strategy of the Prima Management Development Program was considered sufficiently effective in supporting company talent development, although improvements are still needed in the implementation and development aspects of the program